INVESTIGATION ON WELDING EMISSION ESTIMATION IN SHIPYARDS FOR DIFFERENT SHIP TYPES - Celebi, Ugur Bugra (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2014)
Ship building is one of the oldest and heaviest industries. In order to join steel plates appropriately, welding is the most common method during production process, and it is used in approximately every process during ship production. The most applied welding methods are gas metal arc welding (GMAW), shielded metal arc welding (SMAW), flux core arc welding (FCAW), and submerged arc welding (SAW). Most of the particles emitted during welding process are considered as hazardous air pollutants (HAPs). The impacts of these emissions to the environment and human health are well-known and documented. In recent studies, it is stated that welding workers are under a great threat. In this study, an emission factor-based emission estimation model is established and the electrode consumptions of 3 different types of 9 ships are used to make welding emission calculations. The calculations show that the results are independent from ship type and the amount of the welding fume is approximately equal to 2 % of electrodes consumed. The emission estimation methods are suggested on the ratios of length/breadth (L/B) and deadweight ton (DWT) to total consumed electrode weight. L/B and DWT are generally used to classify ships, they are chosen as main parameters to calculate the welding fume. An emission estimation approach is developed for the tankers manufactured in the world during 2012 and 2013, and according to this approach, it is concluded that approximately 3500 tons of harmful welding fume were emitted to the atmosphere just from the operation of shielded metal arc welding (SMAW) of tankers manufactured in the year of 2012.
Keywords: Emission estimation; welding process; welding emissions; Turkey; shipbuilding industry; GMAW MILD-STEEL; HEXAVALENT CHROMIUM; FUME FORMATION; EXPOSURE; GAS; INHALATION; MANGANESE; OZONE; SMAW; Environmental Sciences & Ecology